Influencia de la nueva identidad visual de Taxi Sonrisas en su imagen corporativa percibida por los usuarios de los segmentos B y C del distrito de Trujillo del año 2014. - Reyes Rodríguez, Fiorela Lizett (2016)
The present research work aims to determine the influence of the new visual identity of taxi smiles on their corporate image perceived by users of segments b and c in the District of Trujillo from the year 2014. The research problem is referred to the following question: How influences the new visual identity of Taxi Smiles on their corporate image perceived by users of the segments B and C of Trujillo District in 2014? ; Whose hypothesis is: The new visual identity of Taxi Smiles favorably influences on its corporate image to be perceived as a company that offers reliability and security for users of the segments B and C of Trujillo District in 2014. Study variables are: independent variable: Visual identity and dependent variable: corporate image. Non-experimental research design was used, is cross-sectional data were taken at a single point in time, and is causally because it establishes relations of cause between the variables. The survey was applied as data collection techniques. The population consisted of 942,729 people of Trujillo District according to socioeconomic status consists of the B segment is equivalent to a 5.2 % (49,022 people) and the C segment with a 18.2 % (171,577 people), making a total of 220,599. Among the most important results of the study are considered:  In the B-segment, we can appreciate that 74% of customers meet the new logo and in the C-segment, there is a similar percentage of 69% who also has knowledge of the changing of a new logo. Deducing that customers are rapidly capturing this change of visual identity of Taxi smiles.  A significant percentage of 57% in the segment B and 52% in the C-segment, demonstrating that they are agreed that the new Logo of Taxi smiles conveys them that it is a solid, serious and reliable company.  The most valued attribute is the trust that offers the service of Taxi smiles having a 48% in the segment B and 46% in the Csegment, followed we find security with 22% in the segment B and 25% in the segment C. It is concluded that the new visual identity of Taxi smiles influences positively its corporate image to be perceived by the segments B and C as a company that provides confidence and security.